Can't not won't : a story about a child who couldn't go to school - Fricker, Eliza (Jessica Kingsley Publishers, 2023)
"Eliza Fricker gets it. Deceptively simple, endearing, humorous and emotional illustrations following a family managing the early stages of school avoidance are designed to help parents feel seen, and empathetic writing and guidance gives essential advice and tips on navigating school avoidance for parents and professionals alike"--Publisher's description.